Analisis Pendapatan Usahatani Brokoli Di Kelurahan Kakaskasen Kecamatan Tomohon Utara Kota Tomohon - Kudibay, Isabella; Dumais, Joachim Noch Karel; Waney, Nordy Fritsgerald Lucky (Sam Ratulangi University, 2023)
This study aims to analyze the income of broccoli farming in Kakaskasen Village, North Tomohon District, Tomohon City. This research was conducted from June to August 2022. The selection of respondents was done deliberately. The data collection method is a survey method. Interview data collection techniques using a questionnaire. The data used are primary data and secondary data. Primary data was collected through interviews based on questionnaires, to four farmers. The secondary data were obtained from research-related institutions, namely the Department of Agriculture and the Village Office. The results showed that the total production cost of broccoli farming calculated per Ha on average per one planting season was IDR13,958,670.- The total income of broccoli farming on average per one growing season was IDR44,531,250.- the average per growing season is IDR30,572,580.- The R/C ratio of broccoli farmers in Kakaskasen Village is 3.1, which means that farming is profitable.